2018
DOI: 10.1177/0361198118773896
|View full text |Cite
|
Sign up to set email alerts
|

Crisis Communication Patterns in Social Media during Hurricane Sandy

Abstract: Hurricane Sandy was one of the deadliest and costliest of hurricanes over the past few decades. Many states experienced significant power outage, however many people used social media to communicate while having limited or no access to traditional information sources. In this study, we explored the evolution of various communication patterns using machine learning techniques and determined user concerns that emerged over the course of Hurricane Sandy. The original data included ~52M tweets coming from ~13M use… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
35
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 64 publications
(35 citation statements)
references
References 59 publications
0
35
0
Order By: Relevance
“…While communication scholars have given attention to social media platforms as a mechanism for communication during disasters (Cheng, 2018;Eriksson & Olsson, 2016;Freberg et al, 2013;Page et al, 2013;Pitt & Treen, 2017;Sadri et al, 2018), findings from this study indicated not all social media platforms are used as communication tools to the same extent. Facebook was the most prominent social media platform used (to a moderate extent) by Extension faculty members and offices to communicate with clientele.…”
Section: Conclusion Implications and Recommendationsmentioning
confidence: 65%
See 1 more Smart Citation
“…While communication scholars have given attention to social media platforms as a mechanism for communication during disasters (Cheng, 2018;Eriksson & Olsson, 2016;Freberg et al, 2013;Page et al, 2013;Pitt & Treen, 2017;Sadri et al, 2018), findings from this study indicated not all social media platforms are used as communication tools to the same extent. Facebook was the most prominent social media platform used (to a moderate extent) by Extension faculty members and offices to communicate with clientele.…”
Section: Conclusion Implications and Recommendationsmentioning
confidence: 65%
“…The prior research supports the idea that Extension offices and faculty members serve as information conduits and situationally rely on various communication mechanisms to deliver information to their clients and the general public depending on the disaster (Cathey et al, 2007;Pitt & Treen, 2017;Sadri et al, 2018;Telg et al, 2007). Florida has been impacted significantly by hurricanes and is likely to be impacted by hurricanes in the future.…”
Section: Purpose and Objectivesmentioning
confidence: 72%
“…For federal agencies, social media was used across different platforms for a variety of purposes (Department of Homeland Security 2013). Recent research has used Twitter data to determine user activities across time and space during Hurricane Sandy (Sadri 2016), identify storm-phase patterns of communication (Sadri et al 2018), gauge evacuation compliance (Martin et al 2017), and follow the progression of perceiving and responding to evolving risks (Demuth et al 2018).…”
Section: Archival Results and Discussionmentioning
confidence: 99%
“…Online social media (such as Facebook, Twitter) can serve as alternative channels to disseminate information to a wider audience. Applications of such crisis informatics can be found in many recent studies using social media data during disasters (Kryvasheyeu et al, 2015;Thom et al, 2016;Sadri et al, 2018). Since crisis informatics is a relatively new field investigating the role of social media during disasters, most studies commonly focus on high-level correlations among the variables of interest when analyzing large-scale data sets (Palen and Anderson, 2016).…”
Section: Rio De Janeiro Brazilmentioning
confidence: 99%